2018
DOI: 10.1039/c8ib00075a
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule tracking in liveYersinia enterocoliticareveals distinct cytosolic complexes of injectisome subunits

Abstract: In bacterial type 3 secretion, substrate proteins are actively transported from the bacterial cytoplasm into the host cell cytoplasm by a large membrane-embedded machinery called the injectisome. Injectisomes transport secretion substrates in response to specific environmental signals, but the molecular details by which the cytosolic secretion substrates are selected and transported through the type 3 secretion pathway remain unclear. Secretion activity and substrate selectivity are thought to be controlled by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 56 publications
2
24
1
Order By: Relevance
“…In the cytosol, SctK/Q/L/N form a dynamic adaptive network, with a variety of complexes of different stoichiometries that change their composition in response to different external conditions 18 , 25 . Strikingly, protein interactions and exchange rates amongst the cytosolic components correlate with the activity of the injectisome 18 , 24 , 26 . However, the precise role of the cytosolic components in the secretion process remains unclear to this date.…”
Section: Introductionmentioning
confidence: 99%
“…In the cytosol, SctK/Q/L/N form a dynamic adaptive network, with a variety of complexes of different stoichiometries that change their composition in response to different external conditions 18 , 25 . Strikingly, protein interactions and exchange rates amongst the cytosolic components correlate with the activity of the injectisome 18 , 24 , 26 . However, the precise role of the cytosolic components in the secretion process remains unclear to this date.…”
Section: Introductionmentioning
confidence: 99%
“…translating fraction, or if a putative SRP/FtsY/ribosome NC complex can form within the cytosol. We generated speed maps of Ffh, FtsY, and L1, considering the apparent diffusion D * (Rocha et al, 2018;Banaz et al, 2019) obtained from the linear fit of MSD curves on the first 4 time points (t = 1. . .,4• t).…”
Section: Visualization Of the Preferred Subcellular Location Of Distinct Mobility Fractions Shows That Putative Srp/ftsy/ribosome Transitmentioning
confidence: 99%
“…A subsequent PALM analysis in S PI‐1 noted a similar cellular distribution for the sorting platform components (Zhang et al, 2017), indicating that the presence of cytosolic sorting platform proteins and subunit exchange is a universal feature of injectisomes. Fluorescence correlation spectroscopy (FCS) (Diepold et al, 2017) and high‐throughput single‐molecule tracking (Rocha et al, 2018) revealed distinct subcomplexes of the cytosolic T3SS components with different stoichiometries. A combined small angle X‐ray scattering (SAXS)/quantitative mass spec analysis characterized several of these complexes, with the most prominent having a stoichiometry of SctQ‐Qc 2 ‐L 2 ‐N and (SctQ‐Qc 2 ) 2 ‐L 2 ‐N, respectively (Bernal et al, 2019).…”
Section: Protein Dynamics In the T3ssmentioning
confidence: 99%